2022
DOI: 10.3389/fpubh.2021.776940
|View full text |Cite
|
Sign up to set email alerts
|

What Does “Good” Community and Public Engagement Look Like? Developing Relationships With Community Members in Global Health Research

Abstract: Community and public engagement (CPE) is increasingly becoming a key component in global health research. The National Institute for Health Research (NIHR) is one of the leading funders in the UK of global health research and requires a robust CPE element in the research it funds, along with CPE monitoring and evaluation. But what does “good” CPE look like? And what factors facilitate or inhibit good CPE? Addressing these questions would help ensure clarity of expectations of award holders, and inform effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Laying out principles of co‐production and ethical standards is integral to good engagement and involvement with YP 17 . However, exactly how to enact these through participatory and involvement methodologies, how to ‘judge’ whether they have been met, and how this relates to YCoRs interpretations of what is meaningful, is often not formally set out for research programmes 18–20 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laying out principles of co‐production and ethical standards is integral to good engagement and involvement with YP 17 . However, exactly how to enact these through participatory and involvement methodologies, how to ‘judge’ whether they have been met, and how this relates to YCoRs interpretations of what is meaningful, is often not formally set out for research programmes 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…These are helpful in knowing what to report and instilling thought processes but hold less utility for understanding how to implement or evaluate practices in accessible ways for co‐production with YCoR. Additionally, prescriptive guidelines and checklists may inhibit flexibility and creativity in levels of involvement, roles and methodological approaches to working with diverse YCoR and different communities that can be at the heart of effective youth involvement 13,19,20 . Therefore, documenting procedures and evidencing what YCoR find meaningful to them in context—what they ‘get out’ of being involved in a research project—is important to evolve practices, evaluation and standards, and balance power 12,20,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exactly how to enact these through participatory and involvement methodologies, how to 'judge' whether they have been met, and how this relates to YCoRs interpretations of what is meaningful, is often not formally set out for research programmes. 17,18 Direct benefits to YCoR involved as advisors and/or co-researchers are rarely explored and described, and guidance on how to evaluate such involvement is less well developed. 17 However, a recent rapid evidence review conducted with YP synthesised evidence and reported that 'good involvement' can enhance YCoRs sense of agency and empowerment to: extend their learning and awareness about their own health; increase health-related literacy for themselves and other YP; expand their skills and capabilities in other areas of life; increase career prospects (including an increased motivation to pursue health-related opportunities); and, produce further benefits to broader communities of YP.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, prescriptive guidelines and checklists may inhibit flexibility and creativity in levels of involvement, roles and methodological approaches to suit working with diverse YCoR and different communities that can be at the heart of effective youth involvement. 13,18 Therefore, documenting procedures and evidencing what YCoR find meaningful to them in contextwhat they 'get out' of being involved in a particular research project -is important to evolve practices, evaluation and standards. Case studies detailing different modes to capture the broader value, such as the difference that deeper incorporation of YCoRs phenomenological interpretations make to the research, may also serve to motivate and overcome some perceived barriers for researchers.…”
Section: Introductionmentioning
confidence: 99%